PERFORMANCE OF BENZYLTOLUENE AS PURE HYDROCARBON LIQUID ORGANIC HYDROGEN CARRIER (LOHC) IN STORAGE CYCLES - Rüde, Timo; Preuster, Patrick; Wolf, Moritz; Wasserscheid, Peter (Proceedings of WHEC 2022 - 23rd World Hydrogen Energy Conference: Bridging Continents by H2, 2022)
This study presents benzyltoluene/perhydro benzyltoluene (H0-BT/H12-BT) as favourable liquid organic hydrogen carrier (LOHC) system for potential technical applications. LOHCs can enable safe and efficient hydrogen logistics using the existent fuel infrastructure. Compared with the well-established LOHC systems toluene/methylcyclohexane and dibenzyltoluene/perhydro dibenzyltoluene (H0-DBT/H18-DBT), the H0-BT/H12-BT system combines a similarly high volumetric storage density and excellent robustness in hydrogenation/dehydrogenation cycles with low viscosity for easy handling in colder operation conditions. Herein, we report repeated hydrogenation and dehydrogenation cycles of technical grade LOHCs in semi continuous operation at 290 °C with a commercial platinum on alumina catalyst (Pt/Al2O3). Reaction rates for both, hydrogen uptake and release, are generally found to be higher for H0-BT/H12-BT when compared to the DBT-based LOHC system at identical reaction conditions. By-product formation is low during cycling of the H0-BT/H12-BT system and only small amounts of the dehydrocyclisation products, such as methylfluorene species, are formed that can themselves act as hydrogen carrier.
CRIS-Team Scopus Importer:2023-03-29
Keywords: Benzyltoluene; by-product formation; Chemical Hydrogen Storage; reaction rate; repeated storage cycles